Where Do Orthopaedic Surgery Applicants Match on Their Rank Lists? A Survey of Incoming Residents. Issue 1 (4th January 2023) - Imbergamo, Casey; Sequeira, Sean; Pizzo, Dane; Wright, Melissa; Boucher, Henry
Abstract : Background: The National Resident Matching Program reports match results by rank list position for all specialties in aggregate, but these data have not been previously reported for orthopaedic surgery specifically. The purpose of this study was to determine where orthopaedic applicants match on their rank lists in comparison to the national average for all specialties and to evaluate which factors may influence match results. Methods: This was a cross-sectional survey study distributed to all applicants to a single institution's orthopaedic surgery residency program. Metrics such as match result, USMLE scores, Alpha Omega Alpha (AOA) status, and research productivity, in addition to other applicant-specific traits were captured. Results were stratified by match status and rank list position, with subgroup analyses completed for applicants matching at highly ranked programs (1-3) vs. lower ranked programs (≥ 4). Results: The survey was distributed to 698 applicants with a response rate of 32% (n = 224), with a match rate of 85% (n = 191). Thirty-four percent of respondents matched at their top choice program, 15.2% at their second choice, 9.9% at their third, and 40.8% at their fourth or lower. When comparing the matched to unmatched applicant cohorts, there was a significant difference in number of programs ranked, AOA status, and sex. When comparing applicants who matched at highly ranked (1-3) vs. lower ranked (≥ 4) programs, there was a significant difference in USMLE board scores. Conclusions: Orthopaedic surgery residency applicants are significantly less likely to match at their first choice or within their top 3 choices when compared to the national average for all specialties. Number of contiguous ranks, AOA status, and female sex were found to be associated with successfully obtaining an orthopaedic residency position, whereas USMLE board scores were associated with matching higher on one's rank list, thus resulting in greater match satisfaction. Level of Evidence: III.